Comparison Between the Advanced Cardiac Life Support and Adult Advanced Life Support Protocols: A Simulation-Based Pilot Study - Fawaz Altuwaijri; Abdulaziz Alrabiah; Abdullah Alqarni; Alia Kamal Habash; Mohammad Alghofili; Omar Alotaibi; Mansour Altuwaijri (Emergency Medicine International)
Conclusion: Precharging a defibrillator before a rhythm check during chest compression, in anticipation of a potentially shockable rhythm, reduces the time required for defibrillation and limits interruptions in chest compression during CPR. This practice effectively enhances the CCF. Enhancing the continuity of chest compressions can potentially improve survival rates in ARC.